Menegakkan HAM dan Nilai Pancasila di Era Gen-Z - Ikhsan Ikhsan; Herlina Herlina; Dwi Yana Sepvina Barus; Juleha Juleha (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Therefore, this is the role of Generation Z to help enforce human rights. For those who are still unfamiliar with the term Gen-Z, Gen-Z is a generational shift from Generation Y, which at that time technology was developing, then now it has shifted to Generation Z or can also be called i-generation, where this generation is up to date on issues that are developing and spread on the internet or social media. This is where the importance of the role of Gen-Z in helping to enforce human rights lies, this can be done by creating a forum or community of human rights enforcers in which ideas can be exchanged and critical thinking can be practiced, observing the surroundings for cases of bullying and helping and protecting victims so that they are willing to speak up about the cases that befell them without being burdened. besides that because Gen-Z is a very tech-savvy generation, we can take advantage of this technology very well, such as making short, interesting and interactive videos so that the content of the video discussing human rights enforcement is easier to accept and understand, creating threads about the importance of knowing human rights, characteristics of human rights violations, types of human rights violations and so on which in the presentation of this thread can be linked to current issues so that they are interesting for the public to read, counseling or seminars/webinars about human rights can also be options to echo human rights enforcement.Let's not ignore this bullying problem. Because if it is not followed up from now on, the problem will get bigger and harder to control. We must immediately protect the victims, guide them, and provide support for them. Because often the victims do not dare to speak up, and only keep it to themselves, it is not uncommon for it to take a life.